2021
DOI: 10.3390/app11052289
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study about Effect of Basalt Fiber, Gradation, Nominal Maximum Aggregate Size and Asphalt on the Anti-Cracking Ability of Asphalt Mixtures

Abstract: There are many parameters that could affect the properties of asphalt mixtures, such as the fiber additive, gradation type, nominal maximum aggregate size (NMAS), and asphalt. To evaluate the influence of these factors on the crack resistance of asphalt mixture, 10 different types of asphalt mixtures were prepared. The indirect tensile asphalt cracking test (IDEAL-CT) and semi-circle bending test (SCB) were adopted to test the anti-cracking ability of the test samples. The parameters of these two test results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…[19]. The chemical or physical stability of basalt fiber is also very good [20][21][22][23]. Therefore, it could act as a very stable additive in the strengthening of the pavement materials.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. The chemical or physical stability of basalt fiber is also very good [20][21][22][23]. Therefore, it could act as a very stable additive in the strengthening of the pavement materials.…”
Section: Introductionmentioning
confidence: 99%
“…Según Lou et al (2021a), las fibras de basalto son materiales fibrosos obtenidos mediante un proceso que implica la fusión y extrusión del basalto, una roca ígnea de origen volcánico. En este procedimiento, el basalto se somete a altas temperaturas, generalmente alrededor de 1500 °C.…”
Section: Definición Y Origen De Las Fibras De Basaltounclassified
“…Lou et al [ 71 ] analyzed the effect of different aggregate grades on the crack resistance of BF reinforced asphalt mixes and found that the crack expansion rate of SMA-13 mixes was slower than that of SUP-13 mixes. This phenomenon is because SMA has a dense skeletal structure and can disperse stress.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%